2006
DOI: 10.2131/jts.31.371
|View full text |Cite
|
Sign up to set email alerts
|

Sirc-CVS Cytotoxicity Test: An Alternative for Predicting Rodent Acute Systemic Toxicity

Abstract: -An in vitro crystal violet staining method using the rabbit cornea-derived cell line (SIRC-CVS) has been developed as an alternative to predict acute systemic toxicity in rodents. Seventy-nine chemicals, the in vitro cytotoxicity of which was already reported by the Multicenter Evaluation of In vitro Toxicity (MEIC) and ICCVAM/ECVAM, were selected as test compounds. The cells were incubated with the chemicals for 72 hrs and the IC 50 and IC 35 values (μg/mL) were obtained. The results were compared to the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In both cases, the formation of tight epithelial sheets was not observed. This cell line, which is widely used in studies of cytotoxicity, metabolism and permeation of new drug substances Goskonda et al , 2000; Tak et al 2001;Kitagaki et al 2006), was not able to express a zona occludens in our laboratory. Similar results and findings have been described by Tak et al (2001) and Becker (2006) human corneal epithelial cells and is cultured in serum-free medium, did not show TEER values more than 100 cm 2 , suggesting that the cell layers have weak barrier properties.…”
Section: Resultsmentioning
confidence: 88%
“…In both cases, the formation of tight epithelial sheets was not observed. This cell line, which is widely used in studies of cytotoxicity, metabolism and permeation of new drug substances Goskonda et al , 2000; Tak et al 2001;Kitagaki et al 2006), was not able to express a zona occludens in our laboratory. Similar results and findings have been described by Tak et al (2001) and Becker (2006) human corneal epithelial cells and is cultured in serum-free medium, did not show TEER values more than 100 cm 2 , suggesting that the cell layers have weak barrier properties.…”
Section: Resultsmentioning
confidence: 88%
“…Such approach has been undertaken in the European-funded project ACuteTox, aimed to develop in vitro strategies for the assessment of acute human toxicity (www.acutetox.org). Previous in vitro approaches have demonstrated that general cytotoxicity assays may reasonably predict mammal acute systemic toxicity attaining a level of predicition of 70 -80 % (Halle, 2003;Ekwall et al, 1999;Kitagaki et al, 2006;Clemedson et al, 2006). However, neurotoxic events may underlie acute human toxicity that may not be predicted by using an in vitro test that exclusively relies on cell death, contributing to the observed 20 -30 % lack of predictability.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this concern, many efforts have been made to find acceptable substitutes for the rodent LD 50 test, such as in vitro cytotoxicity assays. [5][6][7][8][9][10][11] Bernson et al 12 proposed a 'Multicentre Evaluation Study of In vitro Cytotoxicity' (MEIC), based on a set of 50 very diverse organic and inorganic chemicals. The MEIC chemicals, as they came to be known, have been widely studied.…”
Section: Introductionmentioning
confidence: 99%